Audit Committee Characteristics and Non-Performing Loans: Moderating Effect of Credit Exposure - Rehmat Ullah (Corresponding Author); Muhammad Waris; Dr. Muhammad Tahir; Usama Shafique (`, 2026)
This study aims to investigate the role of audit committee characteristics in controlling non-performing loans. It also examines the moderating effect of credit exposure on the relationship between the audit committee meeting and non-performing loans. It uses secondary data from listed commercial banks in Pakistan for the period 2016-2024. The one-step system generalized method of moments (GMM) was utilized for the estimation of the results. The findings from a one-step system GMM indicate that audit committee size significantly and negatively affects non-performing loans. It suggests that a larger audit committee improves the quality of loans. Furthermore, credit exposure significantly negatively affects the association between the frequency of audit committee meetings and non-performing loans. This study helps to improve loan quality by strengthening the audit committee characteristics of listed commercial banks. Our findings offer valuable insights for regulators and policymakers of the listed commercial banks to enhance the audit committee’s role in mitigating non-performing loans, thereby promoting a sound banking system. Keywords: Non-Performing Loans, Audit Committee Characteristics, Credit Exposure